KSI based Sensitive Data Integrity Validation Method for Precision Medicine System - Kim, Deuk Hun; Jo, Jeong Seok; Kwak, Jin (2019 International Conference on Platform Technology and Service, PlatCon 2019 - Proceedings, 2019)
Interest in precision medicine in the medical field is increasing through the United States 'Precision Medicine Initiative' announced in 2015. Accordingly, a method for secure and efficient provide of precision medicine services has been continuously studied. Recently, a survey by consulting company shows the importance of verification the integrity of data in decision making is increasing in the analysis of sensitive data of big data size that a key component of precision medicine. Therefore, in this paper, we study integrity validation method of sensitive data by applying signature technology called KSI in precision medicine system.
Keywords: Cloud-based; Data validation; Keyless Signatures Infrastructure; Medical security; Precision Medicine System; Cloud-based Precision Medicine Center; Data Validation; Keyless Signatures Infrastructure; Medical Security; Precision Medicine System